Drip irrigation and crop intensification on dykes of pond for enhanced land and water productivity - Rautaray, S K; Mohanty, S; Pradhan, S; Raychaudhuri, S; Mohanty, R K; Dube, R; Mishra, A (Indian Farming, 2021)
Cost of water harvesting using farm ponds is very high. A large number of water harvesting farm ponds are unutilised due to low volume of harvested water. However, the present study reveals that using drip irrigation for intensively grown dyke crops, pipe conveyance for field crops, and multiple use of water resulted in a net return of ` 70,141/ ha which was higher by 2.3 times as compared to the prevailing practice of rice-fallow in rainfed areas.